Analysis of the Relationship between Physical Activity, Sleep Quality, and Nutritional Status in Adolescents - Saleh, Asmulyati S.; Arifin, Ahmad David Royyifi; Nuimkhayat (Universitas Airlangga, 2025)
Background: The nutritional condition of adolescents is a crucial element of their general health and development, shaped by several factors, including physical activity and sleep quality. Nutritional challenges in East Nusa Tenggara (NTT) encompass both under-nutrition and over-nutrition among adolescents. According to Riskesdas data from 2018, the prevalence of malnutrition among adolescents in NTT was 25.7% for those aged 13-15 years and 26.9% for those aged 16-18 years, while the obesity rate was 16% for adolescents aged 13-15 years. This issue is further intensified by insufficient physical exercise and poor sleep. Despite the existence of several interventions targeting dietary behaviors, the correlation between these elements and nutritional health remains underexplored, particularly in NTT. Objectives: This study aimed to examine the correlation between physical activity, sleep quality, and nutritional status in teenagers aged 15 to 18 years at SMK Negeri 3 Kupang, East Nusa Tenggara. This study sought to determine the primary determinants factors affecting the nutritional status of teenagers, particularly in regions experiencing intricate dietary challenges such as NTT. Methods: This research used a cross-sectional study design, conducted in April 2024 at SMK Negeri 3 Kupang. A total of 221 students were selected using the probability sampling technique. Physical activity was categorized into mild, moderate, and vigorous activities, assessed by the Physical Activity Level (PAL) questionnaire. Sleep quality was assessed via the Pittsburgh Sleep Quality Index (PSQI), while nutritional status was determined by body mass index (BMI). The correlation test was carried out using Goodman and Kruskal gamma and strengthened by the Chi-square test to compare the distribution of nutritional status in various categories of physical activity and sleep quality. Results: This study showed no significant correlation between physical activity, sleep quality, and nutritional status, with a p-value greater than 0.05. Despite variations in exercise levels and sleep quality among groups with differing nutritional statuses, the correlation between these characteristics and nutritional status was not statistically significant. Conclusion: Physical activity and sleep quality alone are sufficient to determine adolescent nutritional health. A more holistic approach that incorporates additional aspects such as nutrition, socioeconomic status, and other characteristics, is required. Effective therapies should focus on enhancing dietary behaviors, augmenting physical activity, managing stress, and fostering improved sleep patterns to elevate adolescent nutritional status.